PWE-033 The outcomes of therapeutic drug monitoring (TDM) in a non-tertiary setting. (8th June 2018) - Kumar, Aditi; Slater, Jayne; Bates, Beth; Jones, Judith; Silva, Shanika De
Abstract : Introduction: Biological therapy is now well established for the treatment of inflammatory bowel disease (IBD). Even though the majority of patients respond to treatment, up to 46% of patients will lose response within twelve months of initiating therapy. TDM has become increasingly beneficial and cost effective in altering management of patients. Methods: We performed a retrospective study of all patients with IBD at the Dudley Group NHS Trust UK who were on either infliximab or adalimumab and had TDM carried out from 2015 onwards during the course of their disease. Patient notes, blood tests, endoscopy reports and clinic letters were used for data collection. Results: 99 patients had TDM carried out at least once whilst on biological therapy. The levels were done either as a routine check or due to patient symptoms (reactive check). 84 patients had Crohn's disease and 15 had ulcerative colitis. The majority of patients were on adalimumab (n=70, 71%). Of the levels that were taken, 16 (16%) had loss of response due to antibody formation, which resulted in 12 (12%) patients changing within class of biologic therapy and 4 (4%) who were switched to out of class. 5 (5%) patients had below therapeutic levels and all had their doses escalated appropriately. 1 patient had a raised level, which led to dose reduction. Of the 77 patients whose levels were therapeutic, 4 patients had their dose escalated due to patient symptoms, 8 patients switched drug (4 had ongoing disease on endoscopic or radiological assessment and 4 had persistent symptoms) and 4 were initiated to step-down therapy. 61 patients continued on the drug and dose they were initiated on. As a result of TDM 38% of patients had an alteration to their treatment, with 16% of these patients receiving biological therapy with no benefit due to antibody formation. Conclusion: Routine drug levels led to change in therapy thereby affecting patient management early on, facilitating disease control in a very complex group of patients. In our study, 21% with therapeutic levels still had a change in therapy indicating levels should not be taken only when questioning loss of response but should be done routinely in all patients on biologic therapy.